ОБРОБКА ІМПУЛЬСНИМ БАР’ЄРНИМ РОЗРЯДОМ ВОДИ В КРАПЕЛЬНОМУ СТАНІ - Божко, І.В.; Кобильчак, В.В. (Інститут електродинаміки НАН України, Київ, 2015)
Energy efficiency of pulse barrier discharge was studied when handling contaminated water in drop state. The study was conducted with three hydrodynamic modes of drops motion, each drop characterized by average drop size diameter of 0,4 mm, 1 mm and 2,5 mm accordingly plus by speed and frequency of dripping. Methylene blue, a persistent organic compound with an initial concentration of 50 mg/l, has served as a water contaminant. Having passed once through discharge camera, decomposition degree of impurities was achieved 40...68 % with the energy yield upto11,3 g/kWh. The drop size diameter and coefficient of the discharge gap filling with drops is ones of the main factors that determines the energy yield of pulse barrier discharge. This coefficient is calculated as the ratio of the total area of all the drops, which are in the discharge gap at the same time, to the area of one of electrodes. For the experimental work conditions this ratio has reached 11,5%. When ratio is reduced to 0,2% the energy yield is down by one order. References 10, table 1, figures 5.